Core-shell catalyst for preparing polyoxymethylene dimethyl ethers through methanol dehydrogenation as well as preparation and application of core-shell catalyst
By designing the core-shell catalyst, the three-layer core-shell structure of acidic molecular sieve, metal active components and aluminum-containing mesoporous silica is solved, and the problems of low selectivity of bifunctional catalyst reactions and fewer high polymerization products are achieved, in-situ coupling of methanol dehydrogenation and condensation reactions are improved, and the selectivity and reaction efficiency of high polymerization products are improved.
Patent Information
- Application Number
- CN202510053228.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-13
AI Technical Summary
In the prior art, the bifunctional catalyst of methanol dehydrogenation to polymethoxydimethyl ether has the problem of low reaction selectivity and fewer high polymerization products.
A core-shell catalyst is designed, including acid molecular sieve, metal active components and aluminum-containing mesoporous silica. By coating the metal active components on the surface of the acid molecular sieve and then coated aluminum-containing mesoporous silica, a three-layer core-shell structure is formed to improve the concentration of formaldehyde and reaction selectivity.
The in-situ coupling of methanol dehydrogenation and methanol and formaldehyde condensation reaction are achieved, which improves the selectivity of high polymerization polymethoxydimethyl ether, simplifies the reaction steps, and reduces energy consumption and production costs.
Smart Images

Figure CN119869600A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst materials, in particular to a core-shell catalyst for preparing polymethoxy dimethyl ether by dehydrogenating methanol, and a preparation method and application thereof. Background Art
[0002] Polyoxymethylene dimethyl ether (PODE) n and DMM n ), whose general formula is CH3O(CH2O) n CH3 (where n is an integer greater than or equal to 1, and is generally less than 8), generally n is 3 to 6 or 3 to 8, is a polyether oligomer, a colorless or light yellow volatile flammable liquid at room temperature, and has a slight ether odor. Polyoxymethylene dimethyl ether has the advantages of high cetane number, high oxygen content, high flash point, low freezing point, and similar physical and chemical properties to diesel. It can be used as a clean diesel blending component that does not contain sulfur and aromatics, and is stably miscible with diesel.
[0003] At present, the traditional synthesis route of polyoxymethylene dimethyl ether is a two-step synthesis route, that is, methyl-terminated raw materials such as methylal and methanol are condensed with oxymethylene raw materials such as gaseous formaldehyde, formaldehyde aqueous solution, trioxymethylene and polyoxymethylene under the catalytic action of an acidic catalyst to obtain the polyoxymethylene dimethyl ether. Chinese patent CN111574340A discloses a system and method for synthesizing polyoxymethylene dimethyl ether from methanol, the system includes a methanol dehydrogenation unit, a formaldehyde absorption unit, an etherification reaction unit and a refining and separation unit connected in sequence, formaldehyde is prepared in the methanol dehydrogenation unit, and then the formaldehyde and methanol are mixed in the etherification reaction unit to synthesize the product polyoxymethylene dimethyl ether. Chinese patent CN1 10054550A discloses a process system and method for producing polyoxymethylene dimethyl ether by gas phase formaldehyde method, wherein methanol is used as raw material, methanol gas is obtained by methanol gasification device, and methanol gas is introduced into methanol dehydrogenation reactor to generate formaldehyde gas and hydrogen under the action of catalyst, then the mixed gas of formaldehyde gas and hydrogen is passed through cooling device to obtain formaldehyde gas at lower temperature, methylal is introduced into methylal preheating device to obtain methylal gas; methylal gas and formaldehyde gas are introduced into gas mixer, and the mixed gas of formaldehyde and methylal is introduced into PODEn reaction tower, and in PODE n Polyoxymethylene dimethyl ether is generated by reaction in the reaction tower under the action of the catalyst.
[0004] The above methods all adopt a two-step synthesis route, first using methanol to dehydrogenate in the presence of a catalyst to prepare formaldehyde, and then using formaldehyde and methanol to condense in the presence of a catalyst to prepare polyoxymethylene dimethyl ether. This method of preparing polyoxymethylene dimethyl ether via a two-step synthesis route has the following disadvantages:
[0005] (1) Complex process: The two-step method needs to be carried out in stages. First, methanol is dehydrogenated to generate formaldehyde, and then the generated formaldehyde is further condensed with methanol to generate the target product, which increases the complexity of equipment and operation.
[0006] (2) High energy consumption: Each step requires specific reaction conditions, such as temperature, pressure, etc., which usually leads to high energy consumption. For example, methanol dehydrogenation is an endothermic reaction, which requires additional energy to drive the reaction; and the subsequent condensation reaction also requires different temperature conditions.
[0007] In view of the shortcomings of the above-mentioned two-step method for synthesizing polyoxymethylene dimethyl ether, researchers continued to study and found that each step requires a catalyst to catalyze the dehydrogenation reaction or condensation reaction. Based on this, the catalysts used in the two steps are integrated together, which can couple the two-step reaction into a one-step reaction, thereby reducing process complexity and energy consumption. Under the action of a bifunctional catalyst (having both metal active sites and acid sites), methanol is partially dehydrogenated to formaldehyde at the metal active site, and PODEn is synthesized from methanol and formaldehyde at the acid active site. This route does not involve the separation step of formaldehyde. Formaldehyde directly reacts with methanol in situ to generate PODEn. Therefore, it has the advantages of short reaction route, simple process, and low reaction energy consumption. In addition, hydrogen is released as a high-quality by-product instead of being oxidized to water. Therefore, this route is better than the in-situ preparation of PODEn by methanol oxidation (methanol is oxidized in air or oxygen atmosphere to generate formaldehyde and water, and PODE n Compared with the direct method), it has a high atom economy. The document "Hydrogen-efficient non-oxidative transformation of methanol into dimethoxymethane over a tailored bifunctional Cu catalyst, Sustainable Energy Fuels, 2021, 5, 117" discloses a bifunctional copper / zeolite catalyst that can simultaneously catalyze the dehydrogenation of methanol to form formaldehyde, and then the formaldehyde and methanol condense to obtain polymethoxy dimethyl ether. This is a catalyst for the continuous production of polymethoxy dimethyl ether directly from methanol in the gas phase, in which the metal copper site mainly dehydrogenates methanol, and the zeolite mainly provides acidic sites for the condensation of methanol and formaldehyde to form polymethoxy dimethyl ether. Although the above-mentioned method of integrating two functional catalysts can couple the two-step reaction into a one-step reaction, the above-mentioned catalyst still has the following disadvantages in the one-step preparation of polymethoxy dimethyl ether:
[0008] (1) Bifunctional catalysts need to optimize two different types of reactions at the same time, namely dehydrogenation and condensation, which increases the requirements for catalyst selectivity. If the catalyst is not designed properly, it may lead to more side reactions, such as methanol dehydration to form dimethyl ether, methanol over-dehydrogenation to form CO or CO2, or methanol and formaldehyde to form methyl formate, which will reduce the selectivity and yield of the target product.
[0009] (2) The mass transfer efficiency within the bifunctional catalyst is a key issue. Since formaldehyde is a gaseous product, it needs to be quickly transferred from the dehydrogenation metal site to the acidic site for condensation reaction. If the catalyst structure is poorly designed, formaldehyde may undergo unnecessary side reactions during the transfer process or fail to reach the acidic site in time, thus affecting the reaction rate and selectivity.
[0010] (3) Polyoxymethylene dimethyl ether is divided into PODE with degree of polymerization n=1 n and PODE with degree of polymerization n=3-6 or 3-8 n The preparation process of high-polymerization polyoxymethylene dimethyl ether is a continuous condensation reaction. Formaldehyde and methanol are first used to prepare methylal (DMM), and then DMM reacts with formaldehyde to obtain PODE2. By analogy, PODE n-1 Condensation with formaldehyde to obtain high polymer polyoxymethylene dimethyl ether PODE n . In practical applications, polyoxymethylene dimethyl ether with a high degree of polymerization has the advantages of higher energy density and better combustion characteristics. The above bifunctional catalyst is obtained by compounding metal copper and zeolite in a simple combination method. After the methanol dehydrogenation reaction obtains formaldehyde gas, part of the formaldehyde desorbs and diffuses, and the concentration of the formaldehyde gas decreases. It is easy for the preparation process of methylal to continue on the catalyst surface, and it is difficult to form a continuous condensation reaction. This results in only methylal with a degree of polymerization of 1 in the reaction product, and no products with a high degree of polymerization are detected. Summary of the invention
[0011] The purpose of the present invention is to provide a core-shell catalyst for preparing polyoxymethylene dimethyl ether by dehydrogenation of methanol and its preparation and application, so as to solve the problem that the reaction selectivity of the above-mentioned bifunctional catalyst is not high and the high polymerization degree product is less.
[0012] To achieve the above-mentioned purpose, the first aspect of the present invention provides a core-shell catalyst for dehydrogenating methanol to prepare polyoxymethylene dimethyl ether. The core-shell catalyst comprises an acidic molecular sieve, a metal active component and aluminum-containing mesoporous silica. The acidic molecular sieve serves as a core structure, the metal active component is coated on the surface of the acidic molecular sieve to form a first coating layer, and the aluminum-containing mesoporous silica is coated on the surface of the metal active component to form a second coating layer.
[0013] Aiming at the problem of unreasonable structural design of bifunctional catalysts with methanol dehydrogenation and condensation in the prior art, the present invention designs the structure of the catalyst, firstly using an acidic molecular sieve as the core structure, and then coating the metal active component and aluminum-containing mesoporous silica on its surface in sequence, and after the coating is completed, the entire catalyst presents a core-shell structure. The acidic molecular sieve in the middle and the aluminum-containing mesoporous silica coated on the outermost layer are mainly used as catalytic sites for the condensation reaction of formaldehyde and methanol, while the metal active component between the acidic molecular sieve and the aluminum-containing mesoporous silica is mainly used as the reaction site for methanol dehydrogenation.
[0014] In the actual reaction process, methanol undergoes methanol dehydrogenation reaction with the metal active components of the intermediate layer to obtain formaldehyde. At this time, the formaldehyde is located between the acidic molecular sieve and the aluminum-containing mesoporous silica, forming a confined space for the generated formaldehyde. This confined space can increase the density of formaldehyde in a unit space, which is beneficial to PODE n-1 The accessibility to contact with formaldehyde can significantly promote the chain growth reaction of PODEn and improve the selectivity of high-polymerization PODEn products by regulating the relative ratio of dehydrogenation active sites (metal active sites) and condensation active sites (acidic active sites). In ordinary bifunctional catalysts with acidic sites and metal active sites, only the substance with acidic sites and the substance with metal active sites are simply compounded, and there is no structural design of the three-layer core-shell catalyst in the present invention. In the actual application process of the bifunctional catalyst, methanol is dehydrogenated to generate formaldehyde at the metal active site. Formaldehyde exists in the form of gas and is easily desorbed and diffused from the catalyst, which reduces the concentration of formaldehyde. Only the reaction process of formaldehyde and methanol to generate methylal can continue, and it is difficult to obtain polyoxymethylene dimethyl ether with high polymer in the subsequent continuous condensation reaction process. The present invention utilizes a three-layer core-shell structure to design the catalyst so that the metal active component catalyzes the formaldehyde generated by methanol between the acidic molecular sieve and the aluminum-containing mesoporous silica, which limits the diffusion of formaldehyde gas to a certain extent and increases the concentration of formaldehyde in the confined space, so that the methylal prepared from formaldehyde and methanol can continue to react with formaldehyde to prepare polyoxymethylene dimethyl ether with a high degree of polymerization. The core-shell catalyst of the present invention has good selectivity for polyoxymethylene dimethyl ether with a high degree of polymerization, which is conducive to the application of polyoxymethylene dimethyl ether in diesel blending components.
[0015] Preferably, the dehydrogenation metal active component is at least one of a noble metal and a non-noble metal.
[0016] It should be noted that there are many metal catalysts that can be used for the methanol dehydrogenation reaction to prepare formaldehyde. In principle, commonly used methanol dehydrogenation catalysts can be used as the metal active component of the present invention.
[0017] Preferably, in step (1), the acidic molecular sieve is one of ZSM-5 molecular sieve, BETA molecular sieve, Al-MCM-41 molecular sieve, Al-SBA-15 molecular sieve, and Al-MCM-22 molecular sieve.
[0018] Among them, the silicon-aluminum ratio of ZSM-5 molecular sieve ranges from 25 to 360, the silicon-aluminum ratio of BETA molecular sieve ranges from 25 to 300, the silicon-aluminum ratio of Al-MCM-41 molecular sieve ranges from 25 to 200, the silicon-aluminum ratio of Al-SBA-15 molecular sieve ranges from 25 to 200, and the silicon-aluminum ratio of Al-MCM-22 molecular sieve ranges from 25 to 200.
[0019] The second aspect of the present invention provides a method for preparing a core-shell catalyst, comprising the following steps:
[0020] (1) coating a metal active component on the surface of an acidic molecular sieve to obtain a molecular sieve composite material;
[0021] (2) dispersing the molecular sieve composite material in a mixed solution, then sequentially adding tetraethyl orthosilicate and aluminum nitrate, stirring for reaction, centrifuging, washing, drying and calcining to obtain a nanocomposite material;
[0022] (3) The nanocomposite material is heat treated in a reducing atmosphere to obtain a core-shell catalyst.
[0023] The function of step (1) in the present invention is mainly to load the metal active component onto the acidic molecular sieve. The loading methods of the metal active component well known to those skilled in the art, such as impregnation method, hydrothermal synthesis method, ion exchange method, precipitation method, physical mixing method, chemical vapor deposition method, etc., can be used in the present invention.
[0024] Preferably, in step (1), when the metal active component is a non-precious metal, the raw material of the non-precious metal includes at least one of divalent soluble metal salts and at least one of trivalent soluble metal salts;
[0025] The specific process of coating the metal active components on the surface of the acidic molecular sieve is:
[0026] The acidic molecular sieve is dispersed in deionized water and fully ultrasonically stirred to obtain solution A; a divalent soluble metal salt, a trivalent soluble metal salt and urea are dissolved in deionized water and fully stirred to obtain solution B, and solution B is added dropwise to solution A and stirred continuously to obtain a mixed solution;
[0027] The mixed solution is subjected to a hydrothermal reaction, and after the reaction is completed, it is centrifuged, washed and dried to obtain molecular sieve / M1M2-LDHs;
[0028] The molecular sieve / M1M2-LDHs is calcined to obtain the molecular sieve / M1M2-LDO, which is a molecular sieve composite material, wherein M1 and M2 represent a divalent soluble metal and a trivalent soluble metal, respectively.
[0029] When the metal active component is a non-precious metal, the non-precious metal includes a divalent soluble metal salt and a trivalent soluble metal salt, which is mainly for the in-situ growth of layered double hydroxides (LDHs) on the surface of the acidic molecular sieve. The LDHs are calcined at high temperature to form a composite metal oxide (LDO), and then reduced to form a metal-metal oxide. According to the formation characteristics of LDHs, M 3+ / (M 2+ +M 3+ ) has a molar ratio between 0.17 and 0.33.
[0030] Preferably, in step (1), when the metal active components are non-precious metals and precious metals, the raw material of the non-precious metal includes at least one of divalent soluble metal salts and at least one of trivalent soluble metal salts, and the raw material of the precious metal is at least one of soluble precious metal salts;
[0031] The specific process of coating the metal active components on the surface of the acidic molecular sieve is:
[0032] The acidic molecular sieve is dispersed in deionized water and fully ultrasonically stirred to obtain solution A; a divalent soluble metal salt, a trivalent soluble metal salt and urea are dissolved in deionized water and fully stirred to obtain solution B, and solution B is added dropwise to solution A and stirred continuously to obtain a mixed solution;
[0033] The mixed solution is subjected to a hydrothermal reaction, and after the reaction is completed, the molecular sieve / M1M2-LDHs is obtained after centrifugation, washing and drying;
[0034] The molecular sieve / M1M2-LDHs is immersed in a soluble noble metal salt solution to obtain the molecular sieve / M3-M1M2-LDHs;
[0035] The molecular sieve / M3-M1M2-LDHs is calcined to obtain the molecular sieve / M3-M1M2-LDO, which is the molecular sieve composite material, wherein M3 represents a soluble precious metal.
[0036] The divalent soluble metal salt and the trivalent soluble metal salt in the present invention can generate LDHs in situ on the surface of the acidic molecular sieve through a hydrothermal reaction, but the soluble metal salt of the noble metal is difficult to be coated through the above reaction. Therefore, when loading the noble metal active component, an impregnation method is adopted to immerse the prepared nanocomposite material in a soluble metal salt solution of the noble metal, and adsorb the noble metal on the nanocomposite material to achieve the coating of the noble metal.
[0037] As mentioned above, there are many known methods for loading metal active components on the surface of acidic molecular sieves, but each method has different effects on the distribution of metal active components on the acidic molecular sieve and the subsequent agglomeration of metal active components. Based on this, the present invention specifically loads the metal active components on the surface of the acidic molecular sieve in the form of LDHs, which increases the uniformity of the distribution of the metal active components. After subsequent roasting and calcination, the agglomeration of the metal active components can be further reduced, which is particularly important for improving the catalytic activity of the entire catalyst and can further improve the reaction selectivity.
[0038] It should also be noted that LDHs is coated on the surface of the acidic molecular sieve in its own layered form, which forms a hollow shell structure in the middle layer after being coated with aluminum-containing mesoporous silica. This is the confined space mentioned above.
[0039] Preferably, the temperature of the hydrothermal reaction is 100 to 140° C., and the time is 12 to 24 hours.
[0040] Preferably, the calcination temperature is 400-500° C. and the calcination time is 2-6 hours.
[0041] Preferably, the divalent soluble metal salt is at least one of nickel salt, copper salt, and cobalt salt, the trivalent soluble metal salt is at least one of aluminum salt, iron salt, manganese salt, and chromium salt, and the soluble precious metal salt is at least one of platinum salt, palladium salt, ruthenium salt, and rhodium salt. It should be noted that when the non-precious metal active component is coated on the surface of the acidic molecular sieve, the present invention mainly uses divalent metal ions and trivalent metal ions to react on the surface of the acidic molecular sieve to form LDHs, so as long as it can catalyze the dehydrogenation of methanol and can generate LDHs, it can be used in the present invention, not limited to the divalent soluble metal salts and trivalent soluble metal salts listed above.
[0042] More preferably, the nickel salt is nickel nitrate or nickel chloride, the aluminum salt is aluminum nitrate or aluminum chloride, the copper salt is copper nitrate or copper chloride, the cobalt salt is cobalt nitrate or cobalt chloride, the iron salt is iron nitrate, the chromium salt is chromium nitrate, the platinum salt is chloroplatinic acid, sodium chloroplatinate or potassium chloroplatinate, the ruthenium salt is ruthenium trichloride, the palladium salt is palladium nitrate or palladium acetate, and the rhodium salt is rhodium trichloride.
[0043] Preferably, based on the mass of the reduced metal in the metal active component, the mass ratio of the acidic molecular sieve, the dehydrogenation active component and the aluminum-containing mesoporous silica is 1:0.1-0.4:0.1-0.4.
[0044] Preferably, in step (2), the mixed solution comprises deionized water, ethanol, hexadecyltrimethylammonium bromide and 25 wt % NH 3 ·H 2 O.
[0045] Preferably, in step (2), the calcination temperature is 400-550° C. and the calcination time is 2-6 hours.
[0046] Preferably, in step (2), the silicon-aluminum ratio of the aluminum-containing mesoporous silica is in the range of 25 to 300.
[0047] In step (2) of the present invention, corresponding ethyl orthosilicate and aluminum nitrate can be added according to the silicon-aluminum ratio of aluminum-containing mesoporous silica (Al-MS).
[0048] Preferably, in step (3), the reducing atmosphere is pure hydrogen or a mixture of hydrogen and argon. When the reducing atmosphere is a mixture of hydrogen and argon, the volume ratio of hydrogen to argon is (1-3):(7-9).
[0049] Preferably, in step (3), the heat treatment temperature for the reduction reaction is 400-600° C. and the time is 2-4 hours.
[0050] The third aspect of the present invention provides an application of a core-shell catalyst, which is an application of the core-shell catalyst in the in-situ coupling preparation of polyoxymethylene dimethyl ether by methanol dehydrogenation.
[0051] The reaction process of in-situ coupling of methanol dehydrogenation catalyzed by the core-shell catalyst in the present invention to prepare polyoxymethylene dimethyl ether is as follows:
[0052]
[0053] The first step is the dehydrogenation of methanol, where methanol is catalyzed by metal active sites (metal active components) to generate methanol, and the second step is the condensation reaction, where methanol and formaldehyde react on acidic active sites (acidic molecular sieves and aluminum-containing mesoporous silica) to generate polyoxymethylene dimethyl ether. The two-step reaction can be coupled in situ under the action of a bifunctional catalyst (metal and acidic active site composite catalyst), and finally methanol is reacted in one step to obtain polyoxymethylene dimethyl ether.
[0054] Preferably, the continuous reaction process of methanol dehydrogenation in situ coupling to prepare polyoxymethylene dimethyl ether is as follows:
[0055] The reaction was carried out in a fixed bed reactor. After the core-shell catalyst was formed and pressed, the particles with a particle size of 20-40 mesh were screened and loaded into the reaction tube. The core-shell catalyst bed was heated to 150-260°C under a flowing N2 atmosphere. Subsequently, methanol was quantitatively fed through a high-pressure constant flow pump. The methanol volume space velocity was 0.2-2h based on the liquid phase feed. -1 After methanol is gasified, it is fully mixed with N2 and passed into the reaction tube. The reaction temperature is 120-240°C and the reaction pressure is normal pressure.
[0056] Preferably, the intermittent reaction process of in-situ coupling of methanol dehydrogenation to prepare polyoxymethylene dimethyl ether is as follows:
[0057] The reaction is carried out in a reactor with condensation function or a normal pressure glass reactor. During the reaction, a highly stable and high boiling point solvent is added so that the reaction temperature can reach above the boiling point of methanol. Under argon protection, the reaction temperature is 120-220°C, the reaction time is 0.5-6h, the reaction pressure is normal pressure, and the amount of core-shell catalyst used is 1.5wt% of the mass of methanol.
[0058] Therefore, the present invention adopts the above-mentioned core-shell catalyst for preparing polyoxymethylene dimethyl ether by dehydrogenation of methanol and its preparation and application, which has the following beneficial effects:
[0059] (1) The core-shell catalyst prepared by the present invention is a bifunctional catalyst having an acidic site and a metal active site, which can realize the in-situ coupling of methanol dehydrogenation and methanol-formaldehyde condensation reaction, which not only simplifies the reaction steps but also improves the selectivity and yield of the reaction.
[0060] (2) The core-shell catalyst of the present invention uses the middle acidic molecular sieve and the outermost aluminum-containing mesoporous silica as acidic sites, and the dehydrogenation metal active component in the middle layer as the metal active site. Both have a synergistic effect, which can better control the reaction path, reduce the generation of by-products, and improve the selectivity of the target product.
[0061] (3) The core-shell catalyst of the present invention has a three-layer core-shell structure, with an acidic molecular sieve as the core, a metal-metal oxide (metal active component) as the middle layer, and an outermost layer as a shell structure containing aluminum mesoporous silica. The double-layer acid catalyst surrounds the intermediate metal active site, which promotes the generated intermediate formaldehyde to react with methanol / PODE in a confined space environment. n-1 Condensation reaction occurs at the acidic site, which effectively promotes the chain growth reaction and improves the selectivity of high polymerization products.
[0062] (4) The present invention can effectively regulate the dehydrogenation temperature, dehydrogenation reaction rate and dehydrogenation product selectivity of methanol by regulating the composition of metal active sites; by regulating the type and silicon-aluminum ratio of the molecular sieve core and the silicon-aluminum ratio of the Al-MS shell, the product selectivity of the reaction of methanol and formaldehyde can be regulated, and the formation of by-products such as methyl formate can be effectively avoided; by regulating the relative ratio and distance between the metal active sites and the acid active sites, the composition and selectivity of the products can be effectively regulated, thereby achieving highly selective synthesis of PODEn.
[0063] (5) The present invention uses core-shell catalysts for in-situ coupling of methanol dehydrogenation to prepare polyoxymethylene dimethyl ether, thereby replacing the traditional two-step method with a one-step method, reducing energy consumption and equipment investment, and lowering production costs.
[0064] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 This is a schematic diagram of the structure of the catalyst prepared by the present invention. DETAILED DESCRIPTION
[0066] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0067] Example 1
[0068] The method for preparing a core-shell catalyst for preparing polyoxymethylene dimethyl ether by dehydrogenation of methanol comprises the following steps:
[0069] (1) 1 g of ZSM-5 molecular sieve (silicon to aluminum ratio 300) was dispersed in 30 ml of deionized water, and the mixture was thoroughly sonicated and stirred, which was recorded as solution A; 0.4955 g of nickel nitrate hexahydrate, 0.2131 g of aluminum nitrate nonahydrate, and 0.3070 g of urea were weighed and dissolved in 30 ml of deionized water, and the mixture was thoroughly stirred, which was recorded as solution B; solution B was slowly added dropwise to solution A, and the mixture was stirred for 2 h to obtain a mixed solution;
[0070] (2) placing the mixed solution obtained in step (1) in a hydrothermal reactor and hydrothermally heating at 120° C. for 12 h;
[0071] (3) After centrifuging the product obtained in step (2), taking the solid phase, and repeatedly washing it with deionized water until the filtrate is neutral;
[0072] (4) drying the solid phase obtained after washing in step (3) at 80° C. for 12 h to obtain ZSM-5 molecular sieve / NiAl-LDHs, and calcining it at 500° C. for 3 h to obtain ZSM-5 molecular sieve / NiAl-LDO;
[0073] (5) The ZSM-5 molecular sieve / NiAl-LDO obtained in step (4) is dispersed in a mixed solution containing 40 ml of deionized water, 20 ml of ethanol, 0.12 g of hexadecyltrimethylammonium bromide and 0.40 ml of 25 wt% NH3·H2O, and the mixture is subjected to ultrasonic treatment for 2 h, and then 0.3353 g of tetraethyl orthosilicate and 0.0242 g of aluminum nitrate nonahydrate are added in sequence, and stirring is continued for another 12 h. Finally, after the reaction is completed, the solid is centrifuged from the reaction mixture, washed with deionized water and ethanol in sequence, vacuum dried, and then calcined at 500°C for 3 h to obtain a ZSM-5 molecular sieve / NiAl-LDO@Al-MS nanocomposite material;
[0074] (6) The molecular sieve / NiAl-LDO@Al-MS nanocomposite material in step (5) is reduced at 450°C for 3h in a reducing atmosphere of H2 / Ar=1:9 to obtain a ZSM-5 molecular sieve / Ni-Ab2O3@Al-MS nanocomposite material with exposed metal active sites. The ZSM-5 molecular sieve / Ni-Al2O3@Al-MS nanocomposite material is the three-layer core-shell catalyst designed by the present invention, and its structural schematic diagram is shown in FIG. Figure 1 shown.
[0075] The ZSM-5 molecular sieve / Ni-Al2O3@Al-MS nanocomposite material is used as a catalyst in the in-situ coupling reaction of methanol dehydrogenation to prepare polyoxymethylene dimethyl ether: the catalytic reaction is carried out in a fixed bed reactor and is a continuous reaction. The catalyst is formed and pressed into tablets to screen out particles with a particle size of 20 to 40 mesh, and then loaded into a quartz reaction tube. The catalyst bed is heated to a preset temperature of 150°C under a flowing N2 atmosphere, and then anhydrous methanol is quantitatively fed through a high-pressure constant flow pump, and the methanol volume space velocity is 0.2h -1 After methanol is gasified at 150°C, it is fully mixed with N2 and introduced into the reaction tube for catalytic reaction. The reaction temperature is 120°C and the reaction pressure is normal pressure.
[0076] The calculation showed that the methanol conversion rate was 6.5%, the yield of polyoxymethylene dimethyl ether was 5.1025%, the selectivity of polyoxymethylene dimethyl ether was 78.5%, of which the selectivity of DMM was 42.7%, and the selectivity of PODE was 1.3%. 2-6 The selectivity was 35.8%.
[0077] Example 2
[0078] The method for preparing a core-shell catalyst for preparing polyoxymethylene dimethyl ether by dehydrogenation of methanol comprises the following steps:
[0079] (1) Disperse 1 g of BETA molecular sieve (silicon to aluminum ratio 25) in 30 ml of deionized water, thoroughly sonicate and stir, and record it as solution A; weigh 1.7285 g of cobalt nitrate hexahydrate, 1.1140 g of aluminum nitrate nonahydrate, and 1.6052 g of urea, dissolve them in 30 ml of deionized water, and thoroughly stir, and record it as solution B; slowly drop solution B into solution A, and continue stirring for 2 h to obtain a mixed solution;
[0080] (2) placing the mixed solution obtained in step (1) in a hydrothermal reactor and hydrothermally heating at 120° C. for 12 h;
[0081] (3) After centrifuging the product obtained in step (2), taking the solid phase, and repeatedly washing it with deionized water until the filtrate is neutral;
[0082] (4) drying the solid phase obtained after washing in step (3) at 80° C. for 12 h to prepare BETA molecular sieve / CoAl-LDHs, dissolving 0.1279 g of rhodium trichloride trihydrate in 15 ml of water by an impregnation method, and then impregnating the BETA molecular sieve / CoAl-LDHs, and vacuum drying to obtain BETA molecular sieve / Rh-CoAl-LDHs, which was then calcined at 500° C. for 4 h to obtain a BETA molecular sieve / Rh-CoAl-LDO nanocomposite material;
[0083] (5) The BETA molecular sieve / Rh-CoAl-LDO nanocomposite obtained in step (4) was dispersed in a mixed solution containing 100 ml of deionized water, 50 ml of ethanol, 0.30 g of hexadecyltrimethylammonium bromide and 1.0 ml of 25 wt% NH3·H2O, and the mixture was subjected to ultrasonic treatment for 2 h, and then 0.8595 g of ethyl orthosilicate and 0.0155 g of aluminum nitrate nonahydrate were added in sequence, and stirring was continued for another 12 hours. Finally, after the reaction was completed, the solid was centrifuged from the reaction mixture, washed with deionized water and ethanol in sequence, vacuum dried, and then calcined at 500°C for 4 h to obtain a BETA molecular sieve / Rh-CoAl-LDO@Al-MS nanocomposite;
[0084] (6) The BETA molecular sieve / Rh-CoAl-LDO@Al-MS nanocomposite material in step (5) is reduced at 500°C for 3h in a reducing atmosphere of H2 / Ar=1:9 to obtain a BETA molecular sieve / RhCo-Al2O3@Al-MS nanocomposite material with exposed metal active sites. The BETA molecular sieve / RhCo-Al2O3@Al-MS nanocomposite material is the three-layer core-shell catalyst designed by the present invention, and its structural schematic diagram is shown in FIG. Figure 1 shown.
[0085] The above-mentioned BETA molecular sieve / RhCo-Al2O3@Al-MS nanocomposite material is used as a catalyst in the reaction process of in-situ coupling of methanol dehydrogenation to prepare polyoxymethylene dimethyl ether: the catalytic reaction is carried out in a reactor with a condensing function, and is an intermittent reaction. During the reaction, n-hexadecane is added so that the reaction temperature can reach above the boiling point of methanol. Under argon protection, the reaction temperature is 220°C, the reaction time is 6h, the reaction pressure is normal pressure, and the amount of catalyst used is 5wt% of the mass of methanol.
[0086] According to calculation, the methanol conversion rate was 18.6%, the yield of polyoxymethylene dimethyl ether was 8.6118%, and the selectivity of polyoxymethylene dimethyl ether was 46.3%, among which the selectivity of DMM was 24.5% and the selectivity of PODE2-6 was 21.8%.
[0087] Example 3
[0088] The method for preparing a core-shell catalyst for preparing polyoxymethylene dimethyl ether by dehydrogenation of methanol comprises the following steps:
[0089] (1) 1 g of Al-SBA-15 molecular sieve (silicon-aluminum ratio 200) was dispersed in 30 ml of deionized water, and the mixture was thoroughly sonicated and stirred, which was recorded as solution A; 0.7128 g of cobalt nitrate hexahydrate, 0.3935 g of aluminum nitrate nonahydrate, and 0.5316 g of urea were weighed and dissolved in 30 ml of deionized water and stirred, which was recorded as solution B; solution B was slowly added dropwise to solution A, and stirring was continued for 2 h to obtain a mixed solution;
[0090] (2) placing the mixed solution obtained in step (1) in a hydrothermal reactor and hydrothermally heating at 120° C. for 24 h;
[0091] (3) After centrifuging the product obtained in step (2), taking the solid phase, and repeatedly washing it with deionized water until the filtrate is neutral;
[0092] (4) drying the solid phase obtained after washing in step (3) at 80° C. for 12 h to prepare Al-SBA-15 molecular sieve / CuCr-LDHs, dissolving 0.0313 g of palladium nitrate dihydrate in 15 ml of water by an impregnation method, and then impregnating the mixture on the Al-SBA-15 molecular sieve / CuCr-LDHs, and vacuum drying to obtain Al-SBA-15 molecular sieve / Pd-CuCr-LDHs, which was then calcined at 500° C. for 5 h to obtain Al-SBA-15 molecular sieve / Pd-CuCr-LDO nanocomposite material;
[0093] (5) The Al-SBA-15 molecular sieve / Pd-CuCr-LDO nanocomposite obtained in step (4) is dispersed in a mixed solution containing 160 ml of deionized water, 80 ml of ethanol, 0.48 g of hexadecyltrimethylammonium bromide and 1.60 ml of 25 wt% NH3·H2O, and the mixture is subjected to ultrasonic treatment for 2 hours, and then 1.3791 g of tetraethyl orthosilicate and 0.0166 g of aluminum nitrate nonahydrate are added in sequence, and stirring is continued for another 12 hours. Finally, after the reaction is completed, the solid is centrifuged from the reaction mixture, washed with deionized water and ethanol in sequence, vacuum dried, and then calcined at 500°C for 5 hours to obtain the Al-SBA-15 molecular sieve / Pd-CuCr-LDO@Al-MS nanocomposite;
[0094] (6) The Al-SBA-15 molecular sieve / Pd-CuCr-LDO@Al-MS nanocomposite material in step (5) is reduced at 500°C for 3h in a reducing atmosphere of H2 / Ar=1:9 to obtain an Al-SBA-15 molecular sieve / PdCu-Cr2O3@Al-MS nanocomposite material with exposed metal active sites. The Al-SBA-15 molecular sieve / PdCu-Cr2O3@Al-MS nanocomposite material is the three-layer core-shell catalyst designed by the present invention, and its structural schematic diagram is shown in FIG. Figure 1 shown.
[0095] The above-mentioned Al-SBA-15 molecular sieve / PdCu-Cr2O3@Al-MS nanocomposite material is used as a catalyst in the reaction process of in-situ coupling of methanol dehydrogenation to prepare polyoxymethylene dimethyl ether: the catalytic reaction is carried out in a glass reactor at normal pressure and is an intermittent reaction. n-Dodecane is added during the reaction so that the reaction temperature can reach above the boiling point of methanol. Under argon protection, the reaction temperature is 120°C, the reaction time is 0.5h, the reaction pressure is normal pressure, and the amount of catalyst used is 1wt% of the mass of methanol.
[0096] The calculation showed that the methanol conversion rate was 4.5%, the yield of polyoxymethylene dimethyl ether was 3.159%, and the selectivity of polyoxymethylene dimethyl ether was 70.2%, of which the selectivity of DMM was 36.6%, and the selectivity of PODE was 1.3%. 2-6 The selectivity was 33.6%.
[0097] Example 4
[0098] The method for preparing a core-shell catalyst for preparing polyoxymethylene dimethyl ether by dehydrogenation of methanol comprises the following steps:
[0099] (1) 1 g of Al-MCM-41 molecular sieve (silicon-aluminum ratio 150) was dispersed in 30 ml of deionized water, and the mixture was thoroughly sonicated and stirred, which was recorded as solution A; 1.2388 g of nickel nitrate hexahydrate, 0.1901 g of copper nitrate trihydrate, 0.5097 g of iron nitrate nonahydrate, and 0.6820 g of urea were weighed and dissolved in 30 ml of deionized water, and the mixture was thoroughly stirred, which was recorded as solution B; solution B was slowly added dropwise to solution A, and stirring was continued for 2 h to obtain a mixed solution;
[0100] (2) placing the mixed solution obtained in step (1) in a hydrothermal reactor and hydrothermally heating at 120° C. for 12 h;
[0101] (3) After centrifuging the product obtained in step (2), taking the solid phase, and repeatedly washing it with deionized water until the filtrate is neutral;
[0102] (4) drying the solid phase obtained after washing in step (3) at 80° C. for 12 h to prepare Al-MCM-41 molecular sieve / NiCuFe-LDHs, and calcining it at 500° C. for 3 h to obtain Al-MCM-41 molecular sieve / NiCuFe-LDO nanocomposite material;
[0103] (5) The Al-MCM-41 molecular sieve / NiCuFe-LDO nanocomposite obtained in step (4) is dispersed in a mixed solution containing 80 ml of deionized water, 40 ml of ethanol, 0.24 g of hexadecyltrimethylammonium bromide and 0.80 ml of 25 wt% NH3·H2O, and the mixture is subjected to ultrasonic treatment for 2 h, and then 0.6905 g of tetraethyl orthosilicate and 0.0062 g of aluminum nitrate nonahydrate are added in sequence, and stirring is continued for another 12 hours. Finally, after the reaction is completed, the solid is centrifuged from the reaction mixture, washed with deionized water and ethanol in sequence, vacuum dried, and then calcined at 500°C for 3 h to obtain the Al-MCM-41 molecular sieve / NiCuFe-LDO@Al-MS nanocomposite;
[0104] (6) The Al-MCM-41 molecular sieve / NiCuFe-LDO@Al-MS nanocomposite material in step (5) is reduced at 450°C for 3 h in a reducing atmosphere of H2 / Ar=1:9 to obtain an Al-MCM-41 molecular sieve / NiCu-Fe3O4@Al-MS nanocomposite material with exposed metal active sites. The Al-MCM-41 molecular sieve / NiCu-Fe3O4@Al-MS nanocomposite material is the three-layer core-shell catalyst designed by the present invention, and its structural schematic diagram is shown in FIG. Figure 1 shown.
[0105] The Al-MCM-41 molecular sieve / NiCu-Fe3O4@Al-MS nanocomposite material is used as a catalyst in the in-situ coupling reaction of methanol dehydrogenation to prepare polyoxymethylene dimethyl ether: the catalytic reaction is carried out in a fixed bed reactor and is a continuous reaction. After the catalyst is formed and pressed into tablets, particles with a particle size of 20 to 40 mesh are screened and loaded into a quartz reaction tube. The catalyst bed is heated to a preset temperature of 150°C under a flowing N2 atmosphere, and then anhydrous methanol is quantitatively fed through a high-pressure constant flow pump, and the methanol volume space velocity is 2h- 1 After methanol is gasified at 150°C, it is fully mixed with N2 and introduced into the reaction tube for catalytic reaction. The reaction temperature is 240°C and the reaction pressure is normal pressure.
[0106] The calculation showed that the methanol conversion rate was 20.5%, the yield of polyoxymethylene dimethyl ether was 7.6465%, and the selectivity of polyoxymethylene dimethyl ether was 37.3%, among which the selectivity of DMM was 20.9%, and the selectivity of PODE was 20.9%. 2-6 The selectivity was 16.4%.
[0107] Example 5
[0108] The method for preparing a core-shell catalyst for preparing polyoxymethylene dimethyl ether by dehydrogenation of methanol comprises the following steps:
[0109] (1) 1 g of Al-MCM-22 molecular sieve (silicon-aluminum ratio 100) was dispersed in 30 ml of deionized water, and the mixture was thoroughly sonicated and stirred, which was recorded as solution A; 0.6178 g of cobalt nitrate hexahydrate, 0.6194 g of nickel nitrate hexahydrate, 0.4285 g of ferric nitrate nonahydrate, and 0.5733 g of urea were weighed and dissolved in 30 ml of deionized water, and the mixture was thoroughly stirred, which was recorded as solution B; solution B was slowly added dropwise to solution A, and the mixture was stirred for 2 h to obtain a mixed solution;
[0110] (2) placing the mixed solution obtained in step (1) in a hydrothermal reactor and hydrothermally heating at 120° C. for 12 h;
[0111] (3) After centrifuging the product obtained in step (2), the solid phase is taken and repeatedly washed with deionized water until the filtrate is neutral;
[0112] (4) drying the solid phase obtained after washing in step (3) at 80° C. for 12 h to prepare Al-MCM-22 molecular sieve / CoNiFe-LDHs, and calcining it at 500° C. for 3 h to obtain Al-MCM-22 molecular sieve / CoNiFe-LDO nanocomposite material;
[0113] (5) The Al-MCM-22 molecular sieve / CoNiFe-LDO nanocomposite obtained in step (4) is dispersed in a mixed solution containing 120 ml of deionized water, 60 ml of ethanol, 0.36 g of hexadecyltrimethylammonium bromide and 1.2 ml of 25 wt% NH3·H2O, and the mixture is subjected to ultrasonic treatment for 2 hours, and then 1.0373 g of tetraethyl orthosilicate and 0.0062 g of aluminum nitrate nonahydrate are added in sequence, and the reaction is continued for 12 hours. Finally, after the reaction is completed, the solid is centrifuged from the reaction mixture, washed with deionized water and ethanol in sequence, vacuum dried, and then calcined at 500°C for 3 hours to obtain the Al-MCM-22 molecular sieve / CoNiFe-LDO@Al-MS nanocomposite;
[0114] (6) The Al-MCM-22 molecular sieve / CoNiFe-LDO@Al-MS nanocomposite material in step (5) is reduced at 500°C for 3h in a reducing atmosphere of H2 / Ar=1:9 to obtain an Al-MCM-22 molecular sieve / CoNi-Fe3O4@Al-MS nanocomposite material with exposed metal active sites. The Al-MCM-22 molecular sieve / CoNi-Fe3O4@Al-MS nanocomposite material is the three-layer core-shell catalyst designed by the present invention, and its structural schematic diagram is shown in FIG. Figure 1 shown.
[0115] The above-mentioned Al-MCM-22 molecular sieve / CoNi-Fe3O4@Al-MS nanocomposite material is used as a catalyst in the reaction process of in-situ coupling of methanol dehydrogenation to prepare polyoxymethylene dimethyl ether: the catalytic reaction is carried out in a reactor with a condensing function, and is an intermittent reaction. n-Dodecane is added during the reaction so that the reaction temperature can reach above the boiling point of methanol. Under argon protection, the reaction temperature is 150°C, the reaction time is 3h, the reaction pressure is normal pressure, and the amount of catalyst used is 2w1% of the mass of methanol.
[0116] The calculation showed that the methanol conversion rate was 12.1%, the yield of polyoxymethylene dimethyl ether was 7.5988%, and the selectivity of polyoxymethylene dimethyl ether was 62.8%, among which the selectivity of DMM was 32.1%, and the selectivity of PODE was 1.2%. 2-6 The selectivity was 30.7%.
[0117] Comparative Example 1
[0118] The difference between this comparative example and Example 1 is that the outermost layer of aluminum-containing mesoporous silica is not coated. The preparation method of the core-shell catalyst for preparing polymethoxydimethyl ether by dehydrogenation of methanol comprises the following steps:
[0119] (1) 1 g of ZSM-5 molecular sieve (silicon to aluminum ratio 300) was dispersed in 30 ml of deionized water, and the mixture was thoroughly sonicated and stirred, which was referred to as solution A. 0.4955 g of nickel nitrate hexahydrate, 0.2131 g of aluminum nitrate nonahydrate, and 0.3070 g of urea were weighed and dissolved in 30 ml of deionized water and stirred, which was referred to as solution B. Solution B was slowly added dropwise to solution A, and stirring was continued for 2 h to obtain a mixed solution.
[0120] (2) placing the mixed solution obtained in step (1) in a hydrothermal reactor and hydrothermally heating at 120° C. for 12 h;
[0121] (3) After centrifuging the product obtained in step (2), taking the solid phase, and repeatedly washing it with deionized water until the filtrate is neutral;
[0122] (4) drying the solid phase obtained after washing in step (3) at 80° C. for 12 h to obtain ZSM-5 molecular sieve / NiAl-LDHs, and calcining the solid phase at 500° C. for 3 h to obtain ZSM-5 molecular sieve / NiAl-LDO nanocomposite material;
[0123] (5) The ZSM-5 molecular sieve / NiAl-LDO nanocomposite material in step (4) is reduced at 450° C. for 3 h in a reducing atmosphere of H 2 / Ar=1:9 to obtain a ZSM-5 molecular sieve / Ni-Al 2 O 3 nanocomposite material.
[0124] The above-mentioned ZSM-5 molecular sieve / Ni-Al2O3 nanocomposite material is used as a catalyst in the reaction process of in-situ coupling of methanol dehydrogenation to prepare polyoxymethylene dimethyl ether: the catalytic reaction is carried out in a fixed bed reactor and is a continuous reaction. The above-mentioned catalyst is formed and pressed into tablets, and then sieved to obtain particles with a particle size of 20 to 40 mesh, which are then loaded into a quartz reaction tube. The catalyst bed is heated to a preset temperature of 150°C under a flowing N2 atmosphere. Subsequently, anhydrous methanol is quantitatively fed through a high-pressure constant flow pump, and the methanol volume space velocity is 0.2h-1. After methanol is vaporized at 150°C, it is fully mixed with N2 and then passed into the reaction tube for catalytic reaction. The reaction temperature is 120°C and the reaction pressure is normal pressure.
[0125] The calculation showed that the methanol conversion rate was 5.9%, the yield of polyoxymethylene dimethyl ether was 4.12%, the selectivity of polyoxymethylene dimethyl ether was 69.8%, of which the selectivity of DMM was 63.6%, and the selectivity of PODE was 69.8%. 2-6 The selectivity is 6.2%.
[0126] Therefore, the present invention adopts the above-mentioned core-shell catalyst for preparing polymethoxydimethyl ether by dehydrogenation of methanol and its preparation and application. The prepared core-shell catalyst uses the middle acidic molecular sieve and the outermost aluminum-containing mesoporous silica as acidic sites, and the dehydrogenation metal active component of the middle layer as the metal active site. The two reaction sites are integrated to construct a bifunctional catalyst, thereby realizing the in-situ coupling of methanol dehydrogenation and methanol and formaldehyde condensation reaction, which not only simplifies the reaction steps, but also improves the selectivity and yield of the reaction.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A core-shell catalyst for preparing polyoxymethylene dimethyl ether by dehydrogenation of methanol, characterized in that: The core-shell catalyst includes an acidic molecular sieve, a metal active component and aluminum-containing mesoporous silica. The acidic molecular sieve serves as a core structure, the metal active component is coated on the surface of the acidic molecular sieve to form a first coating layer, and the aluminum-containing mesoporous silica is coated on the surface of the metal active component to form a second coating layer.
2. The core-shell catalyst according to claim 1, characterized in that: The metal active component is at least one of a noble metal and a non-noble metal.
3. The core-shell catalyst according to claim 1, characterized in that: The acidic molecular sieve is one of ZSM-5 molecular sieve, BETA molecular sieve, Al-MCM-41 molecular sieve, Al-SBA-15 molecular sieve and Al-MCM-22 molecular sieve.
4. The method for preparing a core-shell catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Coating metal active components on the surface of acidic molecular sieve to obtain molecular sieve composite materials; (2) dispersing the molecular sieve composite material in a mixed solution, then sequentially adding tetraethyl orthosilicate and aluminum nitrate, stirring for reaction, centrifuging, washing, drying and calcining to obtain a nanocomposite material; (3) The nanocomposite material is heat treated in a reducing atmosphere to obtain a core-shell catalyst.
5. The method for preparing a core-shell catalyst according to claim 4, characterized in that: In step (1), when the metal active component is a non-precious metal, the raw material of the non-precious metal includes at least one of divalent soluble metal salts and at least one of trivalent soluble metal salts; The specific process of coating the metal active components on the surface of the acidic molecular sieve is: The acidic molecular sieve is dispersed in deionized water and fully ultrasonically stirred to obtain solution A; a divalent soluble metal salt, a trivalent soluble metal salt and urea are dissolved in deionized water and fully stirred to obtain solution B, and solution B is added dropwise to solution A and stirred continuously to obtain a mixed solution; The mixed solution is subjected to a hydrothermal reaction, and after the reaction is completed, it is centrifuged, washed and dried to obtain molecular sieve / M1M2-LDHs; The molecular sieve / M1M2-LDHs is calcined to obtain the molecular sieve / M1M2-LDO, which is the molecular sieve composite material.
6. The method for preparing a core-shell catalyst according to claim 4, characterized in that: In step (1), when the metal active components are non-precious metals and precious metals, the raw materials of the non-precious metals include at least one of divalent soluble metal salts and at least one of trivalent soluble metal salts, and the raw materials of the precious metals are at least one of soluble precious metal salts; The specific process of coating the metal active components on the surface of the acidic molecular sieve is: The acidic molecular sieve is dispersed in deionized water and fully ultrasonically stirred to obtain solution A; a divalent soluble metal salt, a trivalent soluble metal salt and urea are dissolved in deionized water and fully stirred to obtain solution B, and solution B is added dropwise to solution A and stirred continuously to obtain a mixed solution; The mixed solution is subjected to a hydrothermal reaction, and after the reaction is completed, the molecular sieve / M1M2-LDHs is obtained after centrifugation, washing and drying; The molecular sieve / M1M2-LDHs is immersed in a soluble noble metal salt solution to obtain the molecular sieve / M3-M1M2-LDHs; The molecular sieve / M3-M1M2-LDHs is calcined to obtain the molecular sieve / M3-M1M2-LDO, which is the molecular sieve composite material.
7. The method for preparing a core-shell catalyst according to claim 4, characterized in that: Calculated based on the mass of reduced metal in the metal active component, the mass ratio of the acidic molecular sieve, the metal active component and the aluminum-containing mesoporous silica is 1:0.1~0.4:0.1~0.
4.
8. The use of the core-shell catalyst according to claim 1, characterized in that: Application of core-shell catalysts in in situ coupling of methanol dehydrogenation to polyoxymethylene dimethyl ethers.
9. The use of the core-shell catalyst according to claim 8, characterized in that: The continuous reaction process of methanol dehydrogenation in situ coupling to prepare polyoxymethylene dimethyl ether is as follows: The reaction was carried out in a fixed bed reactor. After the core-shell catalyst was formed and pressed, the particles with a particle size of 20-40 mesh were screened and loaded into the reaction tube. The core-shell catalyst bed was heated to 120-260°C under a flowing N2 atmosphere. Subsequently, methanol was quantitatively fed through a high-pressure constant flow pump. The methanol volume space velocity was 0.2-2h-1 in terms of liquid phase feed. -1 After methanol is gasified, it is fully mixed with N2 and passed into the reaction tube. The reaction temperature is 120~240℃ and the reaction pressure is normal pressure.
10. The use of the core-shell catalyst according to claim 8, characterized in that: The batch reaction process of methanol dehydrogenation in situ coupling to prepare polyoxymethylene dimethyl ether is as follows: The reaction is carried out in a reactor with condensation function or a normal pressure glass reactor. During the reaction, a highly stable and high boiling point solvent is added so that the reaction temperature can reach above the boiling point of methanol. Under argon protection, the reaction temperature is 120-220°C, the reaction time is 0.5-6h, the reaction pressure is normal pressure, and the amount of core-shell catalyst used is 1-5wt% of the mass of methanol.
Citation Information
Patent Citations
Gaseous formaldehyde process polyoxymethylene dimethyl ether production technical system and method
CN110054550A
System and method for synthesizing polyoxymethylene dimethyl ether from methanol
CN111574340A
Synthetic method of polymethoxy dimethylether
CN103288607A
Magnetic bifunctional catalyst, preparation method therefor and application of magnetic bifunctional catalyst in methanol catalyzed reaction
CN105521798A
Molecular sieve catalyst for preparation of polyoxymethylene dimethyl ethers
CN106513032A
Cited By
Internal acid and external alkali type organic-inorganic hybrid molecular sieve catalyst as well as preparation method and application thereof
CN121591970A
An inner-limited and outer-toxic type core-shell molecular sieve catalyst, a preparation method and application thereof
CN122517090A